Financial Interconnectedness and Financial Sector Reforms in the Caribbean - Ogawa, Sumiko (IMF Working Papers; Working Paper, 2013)
Financial sector linkages have increased continuously in the Caribbean with cross border capital flows and financial conglomerates dominating the financial system. While the greater interconnectedness can heighten systemic risks and likelihood of contagion, it can have positive impacts provided the regional authorities take steps to prevent the systemic risk. In this context, financial sector reform measures aimed at bolstering and harmonizing prudential regulations in line with international best practices, the strengthening and enhancement of financial sector supervision to include cross border linkages through consolidated supervision, increased cooperation across supervisors in the region, and the establishment of deposit insurance and crisis resolution frameworks will be critical to maintain financial sector stability and minimize the repercussions of any negative shocks.